Paternity test in "Mangalarga-Marchador" equines by DNA-fingerprinting - CARLOS EDUARDO ANUNCIAÇÃO; SPARTACO ASTOLFI-FILHO (Pesquisa Agropecuária Brasileira, 2000)
GC-rich molecular minisatellite probes isolated from the human genome have presented a poor ability for individualization in horses. In this study new DNA sequences were isolated which could be used in paternity tests in horses. Genomic DNA from "Mangalarga-Marchador" horses was treated with restriction enzymes that preferentially digest non-repetitive sequences, so preserving the structure where mini and microsatellites are located. Four clones (S01, S05, S07 and S09) selected from a genomic library screened with a (TG)n oligonucleotide showed similar hybridization profiles generating bands of DNA-fingerprinting type. Using these probes the individualization power obtained was 10-8, which is 10(5)fold higher than that obtained with M13, another GC-rich type probe. All clones were efficient in parentage detection in crossbreedings and presented a 27 bp consensus sequence, GTTTCATTTATTATTCTTTGGAAGAAA, which was repeated 12, 18, 11 and 21 times in clones S01, S05, S07 and S09, respectively.